Bcl-x(L) regulates mitochondrial energetics by stabilizing the inner membrane potential - Chen, Ying-bei (The Rockefeller University Press, 2011)
Mammalian Bcl-x(L) protein localizes to the outer mitochondrial membrane, where it inhibits apoptosis by binding Bax and inhibiting Bax-induced outer membrane permeabilization. Contrary to expectation, we found by electron microscopy and biochemical approaches that endogenous Bcl-x(L) also localized to inner mitochondrial cristae. Two-photon microscopy of cultured neurons revealed large fluctuations in inner mitochondrial membrane potential when Bcl-x(L) was genetically deleted or pharmacologically inhibited, indicating increased total ion flux into and out of mitochondria. Computational, biochemical, and genetic evidence indicated that Bcl-x(L) reduces futile ion flux across the inner mitochondrial membrane to prevent a wasteful drain on cellular resources, thereby preventing an energetic crisis during stress. Given that F(1)F(O)–ATP synthase directly affects mitochondrial membrane potential and having identified the mitochondrial ATP synthase β subunit in a screen for Bcl-x(L)–binding partners, we tested and found that Bcl-x(L) failed to protect β subunit–deficient yeast. Thus, by bolstering mitochondrial energetic capacity, Bcl-x(L) may contribute importantly to cell survival independently of other Bcl-2 family proteins.